Decentralization of Governance-A analysis from Good Governance Perspective - Das, Dr. Anita (International Journal For Research In Educational Studies, 2024)
Governance becomes good when the decisions and actions of the government are based on people’s consent, legitimacy and accountability. Good Governance is one of the very essential conditions for the stability and development of the country and well being of its citizens whose priority to poor, advancement of woman, sustain environment and creates needed opportunities for employment. It has realized that good governance is absolutely necessary to provide the greatest good to the greatest number of people. Therefore process of good governance in all level of the government is very much vital for the development of the society. Decentralization is one of the vital prerequisite of good governance; Decentralization is an organizational setting that may improve the efficiency, effectiveness and responsiveness of various level of the government under suitable condition. With decentralization, local people can directly be involved in decisions that affect services in their community. So, Decentralization facilitates, good governance through empowering local people, allowing them to participate in decisions affecting their life. In this paper attempt has been made to discuss the concept of good governance and significance of decentralized planning for good governance. In recent times good governance is increasingly viewed as an essential element of any well functioning society. Good governance includes the mechanisms and processes, which enable a society to achieve more sustainable human development (Report of Planning commission, 2013). Major donors and international financial institutions argued that poor governance is one of the root cause of underdevelopment, poverty etc. Decentralization is one of the vital prerequisite of good governance; Decentralization is an organizational setting that may improve the efficiency, effectiveness and responsiveness of various level of the government under suitable condition. With decentralization, local people can directly be involved in decisions that affect services in their community. So, Decentralization facilitates, good governance through empowering local people, allowing them to participate in decisions affecting their life. In this paper an attempt has been made to discuss the following objectives.